The Lighter Side of Leadership: Exploring the Role of Humor in Balancing Work and Family Demands in Tourism and Hospitality - Ibrahim A. Elshaer; Alaa M. S. Azazz; Abdulaziz Aljoghaiman; Sameh Fayyad; Tamer Ahmed Abdulaziz; Ahmed Emam (Tourism and Hospitality, 2025)
Work–family conflict (WFC) is a common issue faced by employees balancing work and family roles, but research exploring individual strategies to reduce its negative effects has been limited. Leaders’ positive humor is a mutually (leader–subordinates) amusing communication tool in the workplace. It has been shown to enhance peer relationships (coworker socializing (CWS)) and may serve as an effective coping mechanism that mitigates the adverse effects of workplace stress (work–family conflict). This study strives to examine the relationship between leaders’ positive humor (LPH) and work–family conflict (WFC), with coworker socializing (CWS) mediating this relationship and sensitivity to favorable interpersonal treatment (SFIT) moderating the relationship between leaders’ positive humor and coworker socializing in the tourism and hospitality industry. The research addresses a significant gap in previous studies by investigating these variables together. A total of 387 valid questionnaires were collected from employees of five-star hotels and tourism organizations in Egypt. This study employed PLS-SEM to analyze the data. The results showed that leaders’ positive humor negatively impacts work–family conflict, positively influences coworker socializing and that coworker socializing negatively affects work–family conflict. Additionally, coworker socializing mediated the association between leaders’ positive humor and work–family conflict, and sensitivity to favorable interpersonal treatment moderated the relationship between leaders’ positive humor and coworker socializing. This study provides theoretical and practical insights by validating the proposed model based on the Stimulus–Organism–Response (S-O-R) framework and the Conservation of Resources (COR) theory. Regarding practical implications, the study recommends leadership training on the effective use of humor to foster follower socialization and promote work–family balance.